Spatial and temporal variability in aboveground net primary production of uruguayan grasslands - Guido, A., Díaz-Varela, R., Baldassini, P. and Paruelo, J.M. (My University, 2014)
Aboveground net primary production (ANPP) is a variable that integrates many aspects of ecosystem functioning. Variability in ANPP is a key control for carbon input and accumulation in grasslands systems. In this study, we analyzed the spatial and temporal variability of ANPP of Uruguayan grasslands during 2000&ndash2010. We used enhanced vegetation index (EVI) data provided by the MODIS-Terra sensor to estimate ANPP according to Monteith's (1972) model as the product of total incident photosynthetically active radiation, the fraction of the radiation absorbed by green vegetation, and the radiation use efficiency. Results showed that ANPP varied spatially among geomorphological units, increasing from the north and midwest of Uruguay to the east and southeast. Hence, Cuesta Basáltica grasslands were the least productive (399 g DM · m-2 · yr-1), while grasslands of the Sierras del Este and Colinas y Lomas del Este displayed the highest productivity (463 and 465 g DM · m-2 · yr-1, respectively). This pattern is likely related to differences in soil depth and associated variation in water availability among geomorphological units. Seasonal variability in ANPP indicated peak productivity in the spring in all units, but differences in annual trends over the 10-yr study period suggested that ANPP drivers are operating spatially distinct. Understanding the spatial and temporal variability of ANPP of grasslands are prerequisites for sustainable management of grazing systems.
Keywords: enhanced vegetation index, Monteiths model, productivity, Rio de la Plata grasslands